Ijaza of Ibn Marzouq elhafid to Ibrahim ibn fayed alzawawi; analytical reading - dahmani, siham (The Algerian Historical Journal, 2026)
Ijaza is a means of transferring knowledge from the sheikh to the pupil, produced by the Islamic educational system in the Middle Age. Its analysis give a historical benefits necessary to publicize the scientific movement in Islamic civilization. This Ijaza was written by the famous scientist Tlemsan Ibn Marzouq elhafid to his disciple Ibrahim Bin Fa 'id al-Zawawi al-Constantini.